Risk Factors for Male-Perpetrated Domestic Violence in Vietnam Veteran Families in the United States, 1988 - King, Lynda A. ([Verlag nicht ermittelbar], 2001)
The goal of this project was to gain a better understanding of risk factors associated with male-perpetrated domestic violence, partner's mental distress, and child behavior problems. The researchers sought to demonstrate that two important social and health problems, domestic violence and trauma-related psychological distress, were connected. The project was organized into four studies, each of which addressed a specific objective: (1) Variables characterizing the perpetrator's family of procreation were used to determine the pattern of relationships among marital and family functioning, perpetrator-to-partner violence, partner's mental distress, and child behavior problems. (2) The perpetrator's early background and trauma history were studied to establish the degree to which the perpetrator's family of origin characteristics and experiences, childhood antisocial behavior, exposure to stressors in the Vietnam war zone, and subsequent post-traumatic stress disorder (PTSD) symptomatology related to perpetrator-to-partner family violence. (3) The perpetrator's degree of mental distress was examined to ascertain the ways in which the current mental distress of the perpetrator was associated with marital and family functioning, violence, and current mental distress of the partner. (4) Developmental and intergenerational perspectives on violence were used to model a network of relationships explaining the potential transmission of violence across generations, commencing with the perpetrator's accounts of violence within the family of origin and terminating with reports of child behavior problems within the family of procreation. Data for this study came from the congressionally-mandated National Vietnam Veterans Readjustment Study (NVVRS) (Kulka et al., 1990), which sought to document the current and long-term psychological status of those who served one or more tours of duty in the Vietnam theater of operations sometime between August 5, 1964, and May 7, 1975, compared to their peers who served elsewhere in the military during that era and to a comparable group who never experienced military service. This study relied upon data from the National Survey and Family Interview components of the larger NVVRS. Data were collected through face-to-face structured interviews, with some supplementary self-report paper-and-pencil measures. The interview protocol was organized into 16 parts, including portions requesting information on childhood experiences and early delinquent behaviors, military service history, legal problems in the family of origin and postwar period, stressful life events, social support systems, marital and family discord and abusive behaviors, and physical and mental health. This study emphasized four categories of explanatory variables: (1) the perpetrator's accounts of family of origin characteristics and experiences, (2) the perpetrator's conduct and behavior problems prior to age 15, (3) the perpetrator's exposure to war-zone stressors, and (4) mental distress of the perpetrator, with attention to PTSD symptomatology and alcohol abuse. Additionally, the project incorporated four clusters of family of procreation criterion variables: (1) marital and family functioning, (2) perpetrator-to- partner violence, (3) partner mental distress, and (4) child behavior problems. Variables include child abuse, family histories of substance abuse, criminal activity, or mental health problems, relationship as a child with parents, misbehavior as a child, combat experience, fear for personal safety during combat, alcohol use and abuse, emotional well-being including stress, guilt, relationships with others, panic, and loneliness, acts of physical and verbal violence toward partner, children's emotional and behavioral problems, problem-solving, decision-making, and communication in family, and family support.